Virtual Reality (Vr) As E-Commerce Platfrom To Expand Smes Market In Nusa Tenggara Timur - Arya Brehaspati Adisasmito; Achmad Ghazali (CV. Syntax Corporation Indonesia, 2023)
In Indonesia, universities hold a duty to make changes in society, crystalized in the Tridharma Perguruan Tinggi, which comprises: education, research, and community service. In order to fulfill the duty, Institut Teknologi Bandung (ITB), through The Research and Community Service Campus's Institution (The LPPM), annually funds projects to deliver educational programs, research implementation, and joint projects with local institutions around the country. Leading to the research objective and questions, which is market expansion and promotion, then the further to the chapter two deepening on the literature which first to breakdown the conceptual framework and theoretical foundation, using stakeholder mapping as internal analysis and PASTEL as external analysis, aspect that are highlighted in this research is business growth, promotion, digital technology, virtual reality, and market expansion. In chapter 3, to define the solution of the previous objective in expansion and promotion, the way is to make action, which is to make a design of tools that can expand and promote the related SMEs, which is necessary to perform the design thinking process. The result is confirmed to answer the research objectives and questions, which using the VR Gallery platform, the Dekranasda and the local SMEs are promoted to another level of technology and also market segment, which make it automatically expand the market far across outside the region. The result is that the VR Gallery itself is real and present, currently operating.